Erection of a new genus Biura gen. nov., of the subtribe Aolina (Hemiptera: Cicadidae: Cicadinae: Dundubiini) - Lee, Young June; Sanborn, Allen F. (Zootaxa, 2015)
A new genus, Biura gen. nov., is erected within the subtribe Aolina Boulard, 2012, designating Haphsa bicolora Sanborn, 2009 as the type species. This new genus is distinguished from all other genera in Aolina by the light-colored body lacking prominent markings, non-infuscated wings, very small and short male operculum, thin and long uncal lobes, and distinctly prominent basal lobes of the pygofer.